Media use and dream associations between Canadians of differing cultural backgrounds - Gackenbach, Jayne; Gahr, Sarah (My University, 2015)
Canadian students of varying cultural backgrounds took an online survey for course credit examining their dream experiences (Dream Intensity Scale, DIS; Yu, 2010) and history of media use, i.e., social media and video game play. Regression analyses onto the data found that the role of sex and culture, relative to history of media use, was strongest with total DIS scores as well as dream recall and nightmare information, which is often reported in the literature. Media use was also a component of these two dimensions but its role in predicting self-reported dream experiences was stronger for the other types of DIS information. In general the findings with media use seem to fall around age the subject began using social media or gaming as well as their use of MySpace, one of the first social media sites and thus presumably longest used. These findings support Lambrecht, Schredl, Henley-Einion, and Blagrove (2013) in terms of the continuity hypothesis of dreaming and high frequency of an activity resulting in more dream incorporation.
Keywords: video game play; bizarreness; lucid dreaming